Gen. bryg. Zdzisław Wincenty Przyjałkowski (1892-1971). Ostatni dowódca 15. Dywizji Piechoty (Kronika Bydgoska, 2013)
Brigadier general Zdzisław Wincenty Przyjałkowski (1892-1971), in the opinion of general Zygmunt Bohusz-Szyszk, was ”one of the most talented and the most courageous Polish commanders” of the defensive war in the year 1939. His military path led from his service in the Polish Legions (August 1914), through fighting in the defence of Lvov (January-August 1919), participation in the Polish- Soviet war in 1920, command of different units of the Polish Army in the inter-war period (e.g.: 21st Infantry Regiment, 16th Infantry Brigade), studies at the Military Academy (present-day National Defence University) (1921-1923), chiefdom at the Operation Department ”Zachód” (West) of the Chief War Council Bureau, to promotion to brigadier general of the Polish Army (March 19, 1939) and command of the 15th Infantry Division in Bydgoszcz (from August 1939 to the end of September 1939). During the defensive war, he first commanded the 15th Infantry Division and next his Operation Group (15th and 26th Infantry Divisions) within the Army ”Pomorze” of major general Władysław Bortnowski. These units fought in the defence of Bydgoszcz, on the Bzura River, in the Kampinoska Primeval Forest, and in the defence of Warsaw. For the defensive war he was honoured with the Cross of Valour three times, and seven times during his entire military career, which makes the quotation from another equally brave military man from the first sentence of this text surely credible. This article presents the profile of the next general, connected with the 15th Infantry Division from Bydgoszcz. Biographic sketches of the following generals have been published so far: Albin Jasiński, Jan Władysław Chmurowicz, Wiktor Thommee, Władysław Jung, Tadeusz Gałecki, Jan Tabaczyński, and commodore admiral Wacław Kłoczkowski.